2019
DOI: 10.1177/1056789519862331
|View full text |Cite
|
Sign up to set email alerts
|

Structural behavior of the steel fiber reinforced concrete beam under multiple impact loadings: An experimental investigation

Abstract: Steel fiber reinforced concrete (SFRC) has been proved to be an appropriate material to resist extreme dynamic loadings. To explore the structural behavior of the SFRC component under multiple impact loadings, eight beams with continuous rebars were tested with a drop hammer system. Crack patterns were observed while strains of rebar and concrete, deformation of beams, the impact and reaction forces as well as acceleration were recorded during the experiment. The structural performances were analyzed, and infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…However, the reform damage under the second impact was due to the first impact's flexural crack, w duced the shear transfer capacity of the concrete section. Usually, the failure mode of the RC members under repeated impact loading at the same location should be determined by the damage pattern from the very first impact [19]. However, the findings in this research showed that this theory only applies to a specimen without axial load.…”
Section: Damage Patternmentioning
confidence: 71%
See 1 more Smart Citation
“…However, the reform damage under the second impact was due to the first impact's flexural crack, w duced the shear transfer capacity of the concrete section. Usually, the failure mode of the RC members under repeated impact loading at the same location should be determined by the damage pattern from the very first impact [19]. However, the findings in this research showed that this theory only applies to a specimen without axial load.…”
Section: Damage Patternmentioning
confidence: 71%
“…The difference in the energy dissipation of each posterior impact load led to different damage patterns and deformation of the specimens induced by the prior impact. Furthermore, Jin et al [19] reveal that the damage caused by the initial impact determines the total damage pattern of the beam. If repetitive impact occurs in the same area, the original cracks widen.…”
Section: Introductionmentioning
confidence: 99%
“…Under external loads including seismic action, fatigue stress, and dynamic motion, the mechanical properties of HFRC members will suffer an obvious degradation as well because of the continuous growth of initial defects within the concrete matrix, although quite different from the brittle manner of the plain concrete (Brandt, 2008;Abbas et al, 2014;Jin et al, 2020;Zhang et al, 2020). With respect to the potential failure attributed to the accumulation of unrecoverable deformation and irreversible damage, extensive test results have shown that the inclusion of fibers can effectively inhibit the cracking propagation and improve the damage threshold, resulting in a much more ductile failure mode featured with enhanced nonlinear stress-strain behaviors (Xu et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Recently various fiber-reinforced cement based materials, such as high-performance fiber-reinforced cement composites (HPFRCC), ultra-high performance fiber reinforced concrete (UHPFRC), and ultra-high performance steel fiber reinforced concrete (UHP-SFRC), among others, have been developed through the use of concrete with high matrix strength levels of 100 MPa or more with the addition of steel fibers to ensure a high level of protection of structures subjected to blast and impact loadings (Jin et al., 2020; Li et al., 2015; Liu et al., 2018; Wang et al., 2016; Yoo et al., 2017). Here, HPFRCC is referred to as the representative name of these materials in this paper.…”
Section: Introductionmentioning
confidence: 99%